Exploring Factors that Influence Consumers’ Behaviour Toward Second-Hand Clothing Purchase (AFRICAN JOURNAL OF APPLIED RESEARCH, 2025)
Purpose: This study investigated the factors influencing consumers' intentions of buying used clothes. Despite the undeniable rise of used clothing, a clear understanding of the factors influencing consumer purchasing behaviour remains elusive. The research delved into consumer purchasing motivation and how social and economic influencers also affect the choice of consumers buying second-hand clothing.Design/Methodology/Approach: To gather information for the study, open and closed-ended questions were used to assess 136 participants from the Bolgatanga Metropolis using online Google forms.Research Limitation: This study focused on factors influencing consumers to purchase second-hand clothes in the Bolgatanga Metropolis.Findings: The study’s findings revealed that economic reasons, perceived product quality, social and environmental awareness, and peer influence are significant influencers that affect consumer behaviour toward used clothing purchase and use. This study offers a comprehensive knowledge of how these elements interact to promote the acceptance and use of second-hand clothes.Practical Implication: By identifying the factors influencing purchase intentions, retailers and marketers can develop strategies to more effectively target potential second-hand clothing consumers.Social Implication: Outlining these factors can also help policymakers understand consumers’ purchasing intentions and develop effective policies to educate people concerning the devastating consequences of dumping used clothes and the financial expenses that will go into disposing of them using state funds.Originality/ Value: The study is based on the motivators of consumers purchasing second-hand clothes, which either end up at landsides or are burnt after use.
Keywords: Attitude. consumer behaviour. motivation. purchasing. sustainable fashion